Media Smart Apps Creator Based on the SAS (Synthetic Structural Analytical) Method to Improve Phoneme Pronunciation for Lower Grade Students - Maghfiroh, Farikha; Purwati, Panca Dewi; Trimurtini (Jurnal Edutech Undiksha, 2023)
Learning Indonesian makes students less interested in participating in learning because of the use of inappropriate media and learning methods. This causes students to be passive in the learning process, resulting in low student learning outcomes. Teachers should use interesting media to motivate students to improve learning outcomes. This research aims to create a smart app creator media based on synthetic, analytical structural methods to improve the phoneme pronunciation skills of low-grade students. This research includes development research using the Borg and Gall model. The research subjects were first-grade elementary school students, class teachers, and a team of experts. Data analysis techniques use quantitative and qualitative descriptive. The research results obtained were a media test of 97.5% and a material expert of 90%. The effectiveness of the SAS method-based smart apps creator media for improving phoneme pronunciation can be seen from the increase in pretest and post-test scores on the N-Gain Test. The increase in skills obtained from the average pretest (67.22) and posttest (88.56) scores on the small-scale test was 21.38. The large-scale test also experienced an increase in the average pretest (65.67) and posttest (85.43) scores of 19.76. Based on this, it can be concluded that the smart media creator app based on the SAS method can improve students' skills in pronouncing phonemes.